Photodissociation of pyrrole-ammonia clusters by velocity map imaging: Mechanism for the H-atom transfer reaction - Rubio-Lago, L. (2011)
The photodissociation dynamics of pyrrole-ammonia clusters (PyH·(NH3)n, n = 2-6) has been studied using a combination of velocity map imaging and non-resonant detection of the NH 4(NH3)n-1 products. The excited state hydrogen-atom transfer mechanism (ESHT) is evidenced through delayed ionization and presents a threshold around 236.6 nm, in agreement with previous reports. A high resolution determination of the kinetic energy distributions (KEDs) of the products reveals slow (∼0.15 eV) and structured distributions for all the ammonia cluster masses studied. The low values of the measured kinetic energy rule out the existence of a long-lived intermediate state, as it has been proposed previously. Instead, a direct N-H bond rupture, in the fashion of the photodissociation of bare pyrrole, is proposed. This assumption is supported by a careful analysis of the structure of the measured KEDs in terms of a discrete vibrational activity of the pyrrolyl co-fragment. © the Owner Societies 2011.